Return to work of workers without a permanent employment contract, sick-listed due to a common mental disorder: design of a randomised controlled trial - Lammerts, Lieke (BioMed Central, 2014)
BACKGROUND: Workers without a permanent employment contract represent a vulnerable group within the working population. Mental disorders are a major cause of sickness absence within this group. Common mental disorders are stress-related, depressive and anxiety disorders. To date, little attention has been paid to effective return to work interventions for this type of sick-listed workers. Therefore, a participatory supportive return to work program has been developed. It combines elements of a participatory return to work program, integrated care and direct placement in a competitive job. The objective of this paper is to describe the design of a randomised controlled trial to evaluate the cost-effectiveness of this program compared to care as usual. METHODS/DESIGN: The cost-effectiveness of the participatory supportive return to work program will be examined in a randomised controlled trial with a follow-up of twelve months. The program strongly involves the sick-listed worker in the identification of obstacles for return to work and possible solutions, resulting in a consensus based action plan. This plan will be used as a starting point for the search of suitable competitive employment with support of a rehabilitation agency. During this process the insurance physician of the sick-listed worker contacts other caregivers to promote integrated care. Workers eligible to participate in this study have no permanent employment contract, have applied for a sickness benefit at the Dutch Social Security Agency and are sick-listed between two and fourteen weeks due to mental health problems. The primary outcome measure is the duration until first sustainable return to work in a competitive job. Outcomes are measured at baseline and after three, six, nine and twelve months. DISCUSSION: If the participatory supportive return to work program proves to be cost-effective, the social security system, the sick-listed worker and society as a whole will benefit. A cost-effective return to work program will lead to a reduction of costs related to sickness absence. For the sick-listed worker a cost-effective program results in earlier sustainable return to work, which can be associated with both social and health benefits. TRIAL REGISTRATION: The trial registration number and date is NTR3563, August 7, 2012.